Two‐Step Regioselective Synthesis of 3‐(Sulfonylamino)imidazo[1, 2‐a]pyrimidines from 2‐Aminopyrimidines and N‐(2, 2‐Dichloro‐2‐phenylethylidene)arensulfonamides. Issue 29 (29th August 2014) - Rozentsveig, Igor B.; Serykh, Valery Yu.; Chernysheva, Gulnur N.; Kondrashov, Evgeniy V.; Fedotova, Alena I.; Ushakov, Igor A.; Tretyakov, Evgeny V.; Romanenko, Galina V.
Abstract: The reaction of 2‐aminopyrimidines with N ‐(2, 2‐dichloro‐2‐phenylethylidene)arenesulfonamides affords the corresponding products of nucleophilic addition to the azomethine group, N ‐[2, 2‐dichloro‐2‐phenyl‐1‐(heterylamino)ethyl]sulfonamides, in good yields. The latter are easily cyclized to give imidazo[1, 2‐ a ]pyrimidin‐3‐ylsulfonamides in the presence of NaOH, whereas the expected isomeric imidazo[1, 2‐ a ]pyrimidin‐2‐ylsulfonamides are not formed. A tentative mechanism for the formation of annulated heterocyclic derivatives through Dimroth rearrangement has been proposed. Abstract : 2‐Aminopyrimidines react easily with electrophilic N ‐(arylsulfonyl)phenyldichloroacetaldimines to give the corresponding addition products of the amine moiety to the azomethine group. The obtained compounds were successfully utilized to synthesize imidazo[1, 2‐ a ]pyrimidin‐3‐ylsulfonamides regioselectively.